EDUKASI KESEHATAN MENTAL MELALUI NILAI KEISLAMAN DI MAJELIS TAKLIM MASJID AL-IKHLAS DESA CIMANGGU KABUPATEN CILACAP - Sri Mulyani; Kartika Wanojaleni; Novi Nur Afifah; Putri Dhiya Ulhaq; Farchanudin (JMIMAS: JURNAL PENGABDIAN DAN MITRA MASYARAKAT, 2025)
Mental health has become an important issue in modern society, including in Indonesia. This article describes a mental health education program based on Islamic values through majelis taklim (Islamic study gatherings) as a means of empowering religious communities. The activities were carried out by a team of volunteers from INSIMA over two months at Masjid Al-Ikhlas Cimanggu, involving 30 participants. The approach used was participatory qualitative with thematic study methods that integrated the spiritual values of fasting and the concept of mental health. The results showed three main achievements: (1) a 90% increase in participants' understanding of the psychological benefits of fasting, (2) the organic growth of a culture of mental health discussions, and (3) the integration of mental health materials into the study curriculum. This program has proven effective in increasing mental health literacy based on Islamic values, strengthening intervention models in religious communities that are relevant to the local socio-cultural context. This finding provides theoretical and practical contributions to national mental health promotion through the synergy between the religious and health sectors.